Office-Based Intracordal Hyaluronate Injections Improve Quality of Life in Thoracic-Surgery-Related Unilateral Vocal Fold Paralysis. Issue 40 (October 2015) - Fang, Tuan-Jen; Hsin, Li-Jen; Chung, Hsiu-Feng; Chiang, Hui-Chen; Li, Hsueh-Yu; Wong, Alice M.K.; Pei, Yu-Chen
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Thoracic-surgery-related unilateral vocal fold paralysis (UVFP) may cause severe morbidity and can cause profound functional impairment and psychosocial stress in patients with pre-existing thoracic diseases. In-office intracordal hyaluronate (HA) injections have recently been applied to improve voice and quality of life in patients with vocal incompetence, but their effect on thoracic-surgery-related UVFP remains inconclusive. We therefore conducted a prospective study to clarify the effect of early HA injection on voice and quality of life in patients with thoracic-surgery-related UVFP. Patients with UVFP within 3 months after thoracic surgery who received office-based HA injection were recruited. Quantitative laryngeal electromyography, videolaryngostroboscopy, voice-related life quality (voice outcome survey), laboratory voice analysis, and health-related quality of life (SF-36) were evaluated at baseline, and at 1 month postinjection. A total of 104 consecutive patients accepted office-based HA intracordal injection during the study period, 34 of whom were treated in relation to thoracic surgery and were eligible for inclusion. Voice-related life quality, voice laboratory analysis, and most generic quality of life domains were significantly improved at 1 month after in-office HA intracordal injection. No HA-related complications were reported. Single office-based HA intracordal injection is a safe and effective treatment for thoracic-surgery-related UVFP, resulting in immediate improvements in patient quality of life, voice quality, and swallowing ability.